Efficacy of a carrageenan gel in preventing anal human papillomavirus (HPV) infection: interim analysis of the Lubricant Investigation in Men to Inhibit Transmission of HPV Infection (LIMIT-HPV) randomised controlled trial. (17th June 2021) - Laurie, Cassandra; El-Zein, Mariam; Tota, Joseph E; Khosrow-Khavar, Farzin; Tellier, Pierre-Paul; Coutlée, François; de Pokomandy, Alexandra; Franco, Eduardo L
Abstract : Background: Carrageenan, a non-toxic gelling agent derived from red algae, has potent anti-human papillomavirus (HPV) activity in in vitro and animal studies. We assessed, in an interim analysis, the efficacy of a carrageenan-based gel in reducing the risk of new detections of anal HPV among gay, bisexual and other men who have sex with men (gbMSM). Methods: The LIMIT-HPV study (Lubricant Investigation in Men to Inhibit Transmission of HPV Infection) is a phase IIb, double-blind, placebo-controlled randomised controlled trial conducted in Montreal, Canada. gbMSM were randomly assigned (1:1) to receive a carrageenan-based or placebo gel. Participants were instructed to apply the gel to the anus, condom and/or partners' penis before and—as required—during receptive anal intercourse. Questionnaire data and anal samples were collected at 0, 1, 2, 3, 6, 9 and 12 months. We estimated new detections of anal HPV infection(s) detected via Linear Array using Cox proportional hazards models. Results: Participants recruited from February 2016 to December 2019 were randomly assigned to the carrageenan (n=127) or placebo (n=128) arm. The efficacy and safety analyses included 201 and 210 participants. The median follow-up time was 7.6 months (range: 0–28.5) in the carrageenan group and 9.3 months (range: 0–40.7) in the placebo group. The HR for new detections was 1.21 (95% CI 0.86 to 1.70): 69.4% and 65.1% new detections of HPV in the carrageenan and placebo arms, respectively. More adverse events were reported in the carrageenan (59.8%) compared with the placebo (39.8%) arm. Conclusions: The interim analysis did not demonstrate a protective effect of carrageenan on the risk of new detections of anal HPV infection among gbMSM. Carrageenan gel use was associated with a higher proportion of adverse events. Given these findings and the (assumed) low probability that a beneficial effect would be found by the study's end, the trial was terminated as recommended by the Data Safety and Monitoring Board. Trial registration number: NCT02354144 .